2022
DOI: 10.1108/jm2-03-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

A Nash bargaining game data envelopment analysis model for measuring efficiency of dynamic multi-period network structures

Abstract: Purpose A Nash bargaining game data envelopment analysis (NBG-DEA) model is proposed to measure the efficiency of dynamic multi-period network structures. This paper aims to propose NBG-DEA model to measure the performance of decision-making units with complicated network structures. Design/methodology/approach As the proposed NBG-DEA model is a non-linear mathematical programming, finding its global optimum solution is hard. Therefore, meta-heuristic algorithms are used to solve non-linear optimization prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Luo et al (2022) presented a stochastic non-parametric model for evaluating green development efficiency, and the finding showed that the digital economy significantly improves green development efficiency. Gazori-Nishabori et al (2022) presented a Nash Bargaining game DEA model to measure the efficiency of DMUs with a dynamic network structure. The proposed model's applicability was applied to assess the efficiency of the Industrial Management Institute.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Luo et al (2022) presented a stochastic non-parametric model for evaluating green development efficiency, and the finding showed that the digital economy significantly improves green development efficiency. Gazori-Nishabori et al (2022) presented a Nash Bargaining game DEA model to measure the efficiency of DMUs with a dynamic network structure. The proposed model's applicability was applied to assess the efficiency of the Industrial Management Institute.…”
Section: Literature Reviewmentioning
confidence: 99%